2015
DOI: 10.1159/000442216
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness Changes in the Acute Attack Period in Patients with Familial Mediterranean Fever

Abstract: Purpose: The aim of this study was to evaluate choroidal thickness changes during acute attacks of familial Mediterranean fever (FMF). Methods: Fifty patients with FMF and 50 healthy controls were included. Choroidal thickness of each participant was measured at the foveola and horizontal nasal and temporal quadrants at 500-µm intervals to 1,500 µm from the foveola using spectral-domain optical coherence tomography. White blood cell count, erythrocyte sedimentation rate (ESR) and serum levels of fibrinogen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Kaya et al [1] hypothesized that the cause of increase in choroidal thickness may be the temperature control function of the choroid. As mentioned in the methods section of our study [2], body temperature of all patients was within normal limits. The patients were on colchicine treatment and received nonsteroidal anti-inflammatory drugs when they had fever and/or pain.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Kaya et al [1] hypothesized that the cause of increase in choroidal thickness may be the temperature control function of the choroid. As mentioned in the methods section of our study [2], body temperature of all patients was within normal limits. The patients were on colchicine treatment and received nonsteroidal anti-inflammatory drugs when they had fever and/or pain.…”
mentioning
confidence: 76%
“…We read Kaya et al's comments [1] on our article entitled ‘Choroidal Thickness Changes in the Acute Attack Period in Patients with Familial Mediterranean Fever' [2] with great interest. Kaya et al [1] assert that there is no evidence of inflammation in the choroid during the acute phase of familial Mediterranean fever (FMF).…”
mentioning
confidence: 99%
“…We read the current article entitled ‘Choroidal Thickness Changes in the Acute Attack Period in Patients with Familial Mediterranean Fever' by Gundogan et al [1] with great interest. The authors found choroidal thickness (CT) to be increased during the acute phase of familial Mediterranean fever (FMF).…”
mentioning
confidence: 99%
“…We read with interest the article by Gundogan et al entitled ‘Choroidal Thickness Changes in the Acute Attack Period in Patients with Familial Mediterranean Fever' [1]. They concluded that the choroidal thickness was significantly thicker in patients with familial Mediterranean fever (FMF) compared to healthy controls during an acute attack.…”
mentioning
confidence: 99%